Pengembangan Kurikulum Ekonomi dan Akuntansi Syariah di Sekolah (Studi atas Persepsi Guru dan Siswa di SMA Kota Gorontalo) - Niswatin Niswatin; Roy Hasiru; La Ode Rasuli (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This research aims to describe the perception of teachers and students to the curriculum development of Islamic economics and Islamic accounting at secondary school (high school) in the city of Gorontalo and forms of curriculum development. The method involves a survey of teachers and high school students in the city of Gorontalo by using random sampling with certain criteria. Criteria Teachers are teaching on the subjects of economics and accounting, amount of 17 people, while the student is enrolled as a student majoring in social studies subjects who have obtained economic and accounting totalling 200 students. Data were analysed using descriptive frequency test results. The results showed that 74.1% of teachers and 70.18% of students stated strongly agree and agree curriculum sharia economics and accounting is applied or taught at secondary school level (high school) in the city of Gorontalo. The poll results of the teacher find a form of curriculum implementation of economic and accounting sharia entered as a local content of 47%, incorporated into the lessons of Social Sciences (IPS) by 35%, and incorporated into the Standard competency or Basic competence in the subject of economics and accounting as much as 6%.